Peristaltic Mixed Convection Slip Flow of a Bingham Nanofluid Through a Non-Darcy Porous Medium in an Inclined Non-Uniform Duct With Viscous Dissipation and Radiation - El-Dabe, Nabil T. M.; Abou-zeid, Mohamed Y.; Mohamed, Mona A. A.; Abd-Elmoneim, Mohamed M. (Journal of Applied Nonlinear Dynamics, 2026)
In this work, we studied the peristaltic flow of steady non-Newtonian (Bingham model) nanofluid through a non-uniform inclined pipe. Bingham nanofluid flows through a non-Darcy porous medium under the effects of thermal radiation, heat generation, Ohmic dissipation, chemical reaction, mixed convection and thermal diffusion. The mathematical equations which describe the velocity, temperature and nanoparticles concentration are simplified under the assumptions of long wavelength and low Reynolds number. We obtained a semi-analytical solution for the non-dimensional governing equations by using homotopy perturbation method (HPM). The obtained solutions are functions of the entering physical parameters and the effects of these parameters are explained and discussed through a set of figures. It is clear that the physical parameters in our problem play an effective role and control the obtained solutions. On the other hand, the interference between axial velocity distribution and temperature distribution is due to the presence of mixed convection and Ohmic dissipation, it is found that the effect of local temperature Grashof number $G_r$ on the axial velocity $u$ can be controlled by the adjusting the values of Radiation parameter $R$.